2018
DOI: 10.2196/mhealth.9808
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Perspectives on the Theoretical Domains Framework Elements Needed in a Pediatric Health Behavior App: A Crowdsourced Social Validity Study

Abstract: BackgroundMost pediatric studies do not include parent stakeholders in the design of the intervention itself and many pediatric mobile health (mHealth) interventions are not meaningfully disseminated after the trial period ends. Consequently, the consumer desire for mobile apps targeting pediatric health behavior is likely to be met by commercial products that are not based in theory or evidence and may not take stakeholder preferences into account.ObjectiveThe aim was to assess parent preference for mobile ap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 22 publications
(27 reference statements)
1
19
0
Order By: Relevance
“…By explicitly looking for role congruence regarding social influence from parents and health care providers, we found that as co-users, both parents and health care providers are willing to engage in the process and fulfill their role to empower the primary user consistent with the OCM. These findings correspond to the existing studies that highlight the needs of including parents and physicians in the process of mobile health (mHealth) app design and implementation to promote the use of mHealth technologies [52][53][54][55][56][57].…”
Section: Summary Of Insightssupporting
confidence: 88%
See 1 more Smart Citation
“…By explicitly looking for role congruence regarding social influence from parents and health care providers, we found that as co-users, both parents and health care providers are willing to engage in the process and fulfill their role to empower the primary user consistent with the OCM. These findings correspond to the existing studies that highlight the needs of including parents and physicians in the process of mobile health (mHealth) app design and implementation to promote the use of mHealth technologies [52][53][54][55][56][57].…”
Section: Summary Of Insightssupporting
confidence: 88%
“…Second, we propose the role of CHT co-use for overweight to be tailored to the OCM framework that extends the intention to use construct to recognize CHT co-use (intended behaviors for use) by family members (particularly parents) and health care providers as secondary users that simultaneously influence the adoption of CHT for managing overweight in adolescents. Acknowledging the importance of designing a user interface that is appealing to the users and responds to their needs is central in developing user-centered CHT systems [51][52][53][54][55][56][57]. This study's approach to the design of CHT allows for simultaneous use in the management of adolescent obesity across 3 system users.…”
Section: Contributions Of the Studymentioning
confidence: 99%
“…Although crowdsourcing has been used extensively in business, information technology, and more recently public health (11)(12)(13), the application of crowdsourcing to qualitative research related to pediatric health is innovative. Three prior published papers of which we are aware have described the use of online crowdsourcing methodology to conduct qualitative research aimed at understanding the lived experiences of families impacted by pediatric illness (14)(15)(16).…”
Section: Collection Of Crowdsourced Datamentioning
confidence: 99%
“…used in health research to engage stakeholders in identifying unmet needs, barriers to care, and potential solutions (16)(17)(18)(19)(20)(21). A stakeholder advisory council (SAC) consisting of multidisciplinary providers across four hospitals and parents of children with CHD also convened twice-monthly to provide guidance on study methodology and interpretation of results.…”
Section: Research In Contextmentioning
confidence: 99%